Corrosion prediction for shale gas pipelines based on Bayesian network and common cause failure analysis - Gong, Jianhua; Shen, Jun; Wen, Ming; Yang, Kege; Zhou, Jing; Li, Yaping; Zhu, Xingyu (Frontiers in Materials, 2025)
IntroductionDuring the commissioning and operation of shale gas pipelines, multiple perforation accidents caused by internal corrosion have occurred. Research on internal corrosion probability prediction remains limited due to the complexity of its causes.MethodsThis paper establishes an internal corrosion probability prediction model for shale gas pipelines using a Bayesian network model combined with common cause failure analysis.Results and DiscussionThe model was applied to predict internal corrosion in pipelines within a shale gas field in Sichuan Province, China. The prediction results showed a 20% error margin compared to field inspection results.